Original paper Tolerance to heated cow's milk and egg in children with allergy to this food - Krogulska, Aneta; Białek, Jakub; Wąsowska-Królikowska, Krystyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : A total of 75% of children allergic to cow's milk protein and 70% of children allergic to egg white show tolerance to processed milk or eggs. At the same time, it was found that these children represent a milder phenotype of allergy and outgrow it faster. Aim : To evaluate the possibility of acquiring tolerance to heated cow's milk and egg in children with allergy to these food products. Material and methods : The study included 26 children with IgE-mediated food allergy, aged 2.1-5.7 years. Children studied were selected from 378 children diagnosed at the Department of Paediatric Allergology, Gastroenterology and Nutrition of the Medical University of Lodz and in the Clinic of Allergology at the Maria Konopnicka Memorial University Teaching Hospital No. 4 in Lodz based on suspected food allergy. Oral provocation was carried out for over two consecutive days: the 1 st day with heated allergen, the 2 nd day with unheated food allergen. Among the test methods, interview and evaluation of total IgE and specific IgE were also used. Results : Positive allergen provocation with heated allergen was obtained in 8 children (31%), negative in 18 children (69%). Children with negative oral provocation were challenged with unheated food product. A positive result was obtained in 13 children, revealing in this way the children with allergy to the raw product with simultaneous tolerance to the heated product. A negative result of provocation was found in 3 children with a tolerance to both the unprocessed and processed allergen. Conclusions : Most children with IgE-dependent allergy to cow's milk protein or egg white tolerate the heated products of these proteins. Evaluation of the acquisition of tolerance in children with food allergy, depending on diet, requires further study.